PELESTARIAN KEARIFAN LOKAL MELALUI PELATIHAN MENDONGENG BAGI BUNDA P.A.U.D. KELURAHAN DR. SOETOMO, SURABAYA - Samuel Gunawan; Jenny M. Djundjung; Meilinda Meilinda (Institute of Research and Community Outreach - Petra Christian University, 2015)
The Community Service Project funded by the Higher Education IbM grant as reported here was conducted in order to meet the real need of the focus group in terms of training attendants of Early Childhood Education (ECE) in Kelurahan Dr Soetomo, Surabaya to have the competence to tell Nusantara folk tales These skills of storytelling that have been rare and marginalized by the advancement modern means of communication were badly needed by attendants or would-be attendants who are organized under Early Childhood Education (ECE). Through the training, ECE attendants will be enabled to tell Nusantara folktales which are rich in local wisdom as a media of character education for todlers in the local ECE. Such a community service project could also be beneficial if it is disseminated in other focus groups that badly need it in the inner city of Surabaya.